Novel stress increases hypothalamic-pituitary-adrenal activity in mice with a raised bite. (August 2016) - Miyake, Hidekazu; Mori, Daisuke; Katayama, Tasuku; Fujiwara, Shuu; Sato, Yuichi; Azuma, Kagaku; Kubo, Kin-ya
Highlights: CRH mRNA expression was increased 90 min after the bite-raising procedure. AVP mRNA expression was significantly higher 14 days after the bite-raising procedure. Restraint stress significantly increased CRH mRNA expression in bite-raised mice. The bite-raised condition may enhance sensitivity to novel stress. Abstract: Background and objective: In humans, occlusal disharmony may cause various physical complaints, including head and neck ache, stiffness in the shoulder and neck, and arthrosis of the temporomandibular joints. Occlusal disharmony induced by raising the bite in rodents, increases plasma corticosterone levels, which leads to morphologic changes in the hippocampus and altered hippocampus-related behavior. The paraventricular nucleus (PVN) of the hypothalamus regulates the hypothalamic-pituitary-adrenal system. Chronically stressed animals exposed to a novel stress exhibit higher adrenocorticotropic hormone levels than naive control animals. We hypothesized that there would be different response of the corticotrophin releasing hormone (CRH) and arginine vasopressin (AVP) to a novel acute stress with occlusal disharmony. Design: In order to investigate how exposure of mice with occlusal disharmony to a novel acute stress (restraint stress) affects the PVN, we induced occlusal disharmony by raising the vertical dimension of the bite (bite-raised condition) and examined the expression of corticotrophin releasing hormone (CRH) mRNA and arginine vasopressin (AVP) mRNA in mouse PVN. Results: CRH mRNA expression was increased in the PVN of the bite-raised group 90 min after the bite-raising procedure, but the expression was recovered to the control level at 14 days. AVP mRNA expression in the PVN was normal at 90 min, and increased significantly 14 days after the bite-raising procedure. Exposure to restraint stress in the bite-raised mice induced a significant increase in CRH mRNA expression in the PVN. Conclusions: The bite-raising procedure induced a rapid CRH mRNA response and a slower AVP mRNA response in the parvocellular PVN of the hypothalamus. Exposure to a novel stress following the bite-raising procedure further reinforced the CRH stress response. Thus, occlusal disharmony, such as that induced by raising the bite, may be a risk factor for hypersensitivity to a novel stress.